Green Voices Defending Nature and the Environment in American Civic Discourse - Besel, Richard D.; Duffy, Bernard K. (SUNY Press Open Access, 2016)
The written works of nature's leading advocates-from Charles Sumner and John Muir to Rachel Carson and President Jimmy Carter, to name a few-have been the subject of many texts, but their speeches remain relatively unknown or unexamined. Green Voices aims to redress this situation. After all, when it comes to the leaders, heroes, and activists of the environmental movement, their speeches formed part of the fertile earth from which uniquely American environmental expectations, assumptions, and norms germinated and grew. Despite having in common a definitively rhetorical focus, the contributions in this book reflect a variety of methods and approaches. Some concentrate on a single speaker and a single speech. Others look at several speeches. Some are historical in orientation, while others are more theoretical. In other words, this collection examines the broad sweep of US environmental history from the perspective of our most famous and influential environmental figures.